Effect of autologous umbilical cord blood transfusion in the development of retinopathy of prematurity: randomized clinical trial – study protocol - Torrejon-Rodriguez, Laura; Pinilla-Gonzalez, Alejandro; Lara Cantón, Inmaculada; Albiach-Delgado, Abel; Cascant-Vilaplana, Mari Merce; Cernada, María; Kuligowski, Julia; Solves Alcaina, Maria Pilar; Gómez, Inés; Vento, Maximo; Aguar Carrascosa, Marta (Frontiers in Pediatrics, 2023)
Background: Currently, the treatment of anemia in preterm infants is based on packed red blood cell (RBC) transfusions from adult donors. Oxygen (O2) is mainly transported to the tissues bound to hemoglobin (Hb). In extremely low gestational age neonates (ELGANs), fetal hemoglobin (HbF), which has a higher affinity for O2, represents up to 95% of circulating hemoglobin. During the first month of life, the majority of ELGANs will require an adult-donor RBC transfusion causing HbF levels to rapidly drop. HbA releases 50% more oxygen in peripheral tissues than HbF. Increased release of O2 in the retina is one of the main factors related to the development of retinopathy of prematurity (ROP). Collecting umbilical cord blood and using autologous umbilical cord whole blood (UCB) transfusions would contribute to maintaining physiological HbF concentrations in newborns and avoid oxygen-in-excess derived damage. Methods: This is a randomized, double-blinded, multicenter clinical trial. ELGANs ≤ 28 weeks of gestational age will be randomized 1:1 to receive an autologous umbilical cord blood transfusion (intervention arm) or standard transfusion of packed RBC from an adult donor (control arm) to assess ROP development. Assuming a 50% reduction in ROP incidence, 134 patients (67 per group) will be recruited. When blood transfusion is indicated, the Blook Bank will supply UCB or RCB according to the patient’s group. The primary endpoint is the incidence of any ROP. Secondary endpoints are assessessment of treatment safety, results of biomarkers related to ROP and its chronology, and urine oxidative stress markers. In addition, the cellular composition of umbilical cord blood and its relationship with prematurity-related pathologies will be analyzed. All patients will be followed-up to 24 months of corrected age to evaluate their neurodevelopment. Discussion: ROP is a major cause of irreversible blindness in preterm newborns. Transfusions with adult donor blood can lead to complications, including ROP. UCB transfusions offer advantages by maintaining physiological HbF levels and potentially optimizing postnatal development. Moreover, autologous UCB transfusion could reduce risks associated with heterologous blood products, although volume collection remains challenging. UCB contains growth factors and progenitor cells that may impact ROP.